Monitoring movements with high trunk acceleration during badminton games: an approach combining a microsensor unit and video analysis - Sasaki, S.; Nagano, Y.; Shimada, Y.; Ichikawa, H. (British Journal of Sports Medicine, 2021)
Background Stiff landing is associated with increased anterior cruciate ligament (ACL) injury risk, especially in young female athletes. As an alternative to a force platform, a tri-axial accelerometer is a useful tool to reflect the magnitude of the ground reaction force exerted during games.